Water Purification Training for Sejegi Village Community Mempawah Regency - Masriani Masriani; Hairida Hairida; Rahmat Rasmawan; Rody Putra Sartika; Eny Enawaty; Rini Muharini; Ira Lestari; Erlina Erlina; Husna Amalya Melati; Lukman Hadi; Henny Herawaty; Warsidah Warsidah; Maria Ulfa (STKIP Singkawang, 2022)
Sejegi Village, Mempawah Timur District, Mempawah Regency, West Kalimantan is an area with a fairly large peat area, so it is very difficult for people to get clean water sources. On the other hand, PDAM can not fulfill the community's clean water needs, so the people of Sejegi village generally rely on rainwater as a source of clean water. For this reason, water purification training was carried out for the people of Sejegi Village, Mempawah Regency. The purpose of this activity is to improve the skills of the people of Sejegi Village in purifying peat water so that they get clean water that is suitable for household use, as well as to overcome community difficulties in obtaining clean water sources during the dry season. The training was carried out using a lecture method and demonstration of making a mini water treatment installation using large buckets and cans of used paint, fibers, gravel, whiting, alum and PAC. The training was attended by 30 residents of the Sejegi Village community. The results of the training showed that the community's understanding of the importance of clean water increased after being given the training. In addition, skills in designing water purification with simple materials are also starting to appear. This training is expected to help the Sejegi Village community in solving problems with clean water sources that are suitable for use.